REPRESENTASI GENDER DALAM CERITA TEMATIK BILINGUAL AKU CINTA KEBERSIHAN KARYA RIAN F. RAHMAN - Sari, Bernadeta; Miranda, Dian; Linarsih, Andini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Gender representation in children's story books, especially bilingual thematic storybooks to find out how gender is depicted in children's stories. This type of research uses the data analysis content of the Miles and Huberman models. The sample/subject in this study was a bilingual story book written by Rian F. Rahman. In the bilingual thematic story I Love Cleanlines (I Love Cleanlines), the researcher saw that in the children's story there are roles of men, namely fathers, boys and girls, namely mothers. Based on the results of the analysis of bilingual thematic storybooks "I Love the Environment (I Love Cleanliness)" related to gender representation, the researchers divided male and female gender, namely roles, behavior, mentality, and emotional characteristics according to the Women's Studies Encyclopedia, it can be concluded that the story has each section according to gender. Even so, this story book is more dominant in providing positions and homework which shows that the role of men is superior, this can be proven by the appearance of men who dominate in every housework such as sweeping, mopping, cleaning windows, and pulling grass. Meanwhile, the role of women only appeared once when delivering food and drinks.